2020
DOI: 10.1177/1932296820942307
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Simple Bedside Wound Characteristics for a Prediction Model for Diabetic Foot Ulcer Outcomes

Abstract: Background: Evidence-based learning systems built on prediction models can support wound care community nurses (WCCNs) during diabetic foot ulcer care sessions. Several prediction models in the area of diabetic foot ulcer healing have been developed, most built on cardiovascular measurement data. Two other data types are patient information (i.e. sex and hemoglobin A1c) and wound characteristics (i.e. wound area and wound duration); these data relate to the status of the diabetic foot ulcer and are easily acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…It should be noted that the six selected variables are those shown to be the best outcome predictors of a given treatment. 21 In other words, if the purpose, for example, had been to find visually similar cases, other variables would probably have been selected.…”
Section: Case-based Reasoning Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the six selected variables are those shown to be the best outcome predictors of a given treatment. 21 In other words, if the purpose, for example, had been to find visually similar cases, other variables would probably have been selected.…”
Section: Case-based Reasoning Systemmentioning
confidence: 99%
“…A newly published retrospective cohort study showed how variables in the form of on-site wound characteristics or easily accessible information collected during wound care consultations are highly informative when it comes to predicting whether a diabetic foot ulcer will heal or not. 21 The data and principles used in that study could provide the basis of an evidence-based learning system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many amputations in people with diabetes are thought to be preventable through education, self-management, and ongoing supervision by health care professionals [5]. To prevent amputations, patients must seek care soon after a problem is identified, because small wounds that are treated early are more likely to heal [6]. Untreated wounds are more likely to become infected and require an amputation to prevent spread to contiguous structures.…”
Section: Introductionmentioning
confidence: 99%
“…One of the severe, formidable complications of DM is diabetic foot syndrome (DFS), together with diabetic retinopathy, nephropathy, neuropathy, and damage to the cardiovascular system. Foot problems occur in a significant number of patients with diabetes, while peripheral arterial lesions occur in 50% of patients with DFS, which is the main cause of poor outcomes in this category of patients ( 1 , 2 ). Progressive deterioration of blood supply to the lower extremities with simultaneous infections associated with wounds and cracks due to various microtraumas of the foot, and insignificant and invisible even for the patient, results in the development of purulent and necrotic complications in the feet, which together with the progression of concomitant diseases, further increases the risk of negative outcomes by increasing the frequency of high amputations of the limbs due to gangrene at the level of the foot, lower leg, and thigh ( 3 - 5 ).…”
Section: Introductionmentioning
confidence: 99%